Modeling analysis of subthreshold voltage signaling along hippocampal mossy fiber axons - Kamiya, Haruyuki (Frontiers in Cellular Neuroscience, 2022)
Axons are classically thought of as electrically well isolated from other parts of the neurons due to the shape of a long cable-like structure. In contrast to this classical view on axonal compartmentalization, recent studies revealed that subthreshold depolarization of soma and dendrite passively propagates to the axons for a substantial distance, as demonstrated in some experimentally accessible axons including hippocampal mossy fibers and cortical pyramidal cell axons. Passive propagation of subthreshold dendritic EPSPs to the axons, defined as EPreSPs (excitatory presynaptic potentials), has been demonstrated to affect transmitter release from the axon terminals. To further characterize and explore the functional significance of passive subthreshold voltage signaling along the axons, the model of EPreSPs along hippocampal mossy fibers, proposed by Alle and Geiger, was reconstructed on the NEURON simulator. To test the effect of EPreSPs on action potentials and transmitter release from the axon terminals, additional conductances were incorporated into the previous passive propagation model. These include the axonal sodium, potassium, and leak channels as well as presynaptic calcium channels composed of P/Q-, N-, and R-types, which are reconstructed from the properties of those recorded from mossy fiber boutons experimentally. In this revised model, the preceding subthreshold EPreSPs slightly reduced the action potential-evoked presynaptic calcium currents by a decrease in the amplitude of action potentials due to the slow depolarization. It should be mentioned that EPreSPs by themselves elicited small calcium currents during subthreshold depolarization through these high-voltage activated calcium channels. Since the previous experimental study by simultaneous pre and postsynaptic recordings demonstrated that EPreSPs enhanced action potential-evoked transmitter release from the mossy fiber terminals, it has been suggested that different mechanisms from the enhancement of action potential-evoked presynaptic calcium entry may involve enhanced transmitter release by EPreSP. Small calcium entry by subthreshold EPreSPs may enhance transmitter release from the mossy fiber terminals by acting as high-affinity calcium sensors for enhancing transmitter release. Another form of axonal subthreshold voltage signaling, GABA-EPreSPs elicited by a spillover of GABA from surrounding interneurons, was also explored. Functional consequences of the two modes of axonal subthreshold voltage signaling were discussed with the simulation results.